INTERJEKSI DALAM BAHASA MELAYU DIALEK SAMBAS - Abrora, Nur Khansa; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research provides insight into how intercourse or exclamation. The word interjection is used to represent the heart of the speaker, though only by using certain words from Sambas dialect Malay language in Sungai Pangkalan Village, Sungai Raya Subdistrict, Bengkayang District. The problem in this research is how the form of interjection, the meaning of interjection, and the function of Sambas dialect malay language. Based on data analysis, this study yields a conclusion (a) Interjection Form in Malay language Sambas dialect has forty two basic words and eleven derivative words. (b) The meaning of interjection in Sambas dialect Malay is twenty-four. (c) Interjection functions in Sambas dialect Malay language are thirty-four, these functions include: thirty-four emotive functions, nineteen conative functions, five fatik functions, and three referential functions. Keywords: Interjection, Form, Function, Sambas Malay